Human aspartic protease memapsin 2 cleaves the β-secretase site of β-amyloid precursor protein - Lin, Xinli (The National Academy of Sciences, 2000)
The cDNAs of two new human membrane-associated aspartic proteases, memapsin 1 and memapsin 2, have been cloned and sequenced. The deduced amino acid sequences show that each contains the typical pre, pro, and aspartic protease regions, but each also has a C-terminal extension of over 80 residues, which includes a single transmembrane domain and a C-terminal cytosolic domain. Memapsin 2 mRNA is abundant in human brain. The protease domain of memapsin 2 cDNA was expressed in Escherichia coli and was purified. Recombinant memapsin 2 specifically hydrolyzed peptides derived from the β-secretase site of both the wild-type and Swedish mutant β-amyloid precursor protein (APP) with over 60-fold increase of catalytic efficiency for the latter. Expression of APP and memapsin 2 in HeLa cells showed that memapsin 2 cleaved the β-secretase site of APP intracellularly. These and other results suggest that memapsin 2 fits all of the criteria of β-secretase, which catalyzes the rate-limiting step of the in vivo production of the β-amyloid (Aβ) peptide leading to the progression of Alzheimer's disease. Recombinant memapsin 2 also cleaved a peptide derived from the processing site of presenilin 1, albeit with poor kinetic efficiency. Alignment of cleavage site sequences of peptides indicates that the specificity of memapsin 2 resides mainly at the S(1)′ subsite, which prefers small side chains such as Ala, Ser, and Asp.